Ecology meets reproductive medicine in HIV prevention: the case for geography-informed approaches for bacterial vaginosis in Africa - Passmore, Jo-Ann S.; Ngcapu, Sinaye; Gitome, Serah; Kullin, Brian R.; Welp, Kirsten; Martin, Darren P.; Potloane, Disebo; Manhanzva, Monalisa T.; Obimbo, Moses M.; Gill, Katherine; Fevre, Mellissa Le; Happel, Anna-Ursula; et al. (Frontiers in Reproductive Health, 2024)
Purpose of reviewWomen in Africa bear the burden of the HIV epidemic, which has been associated with the high prevalence of bacterial vaginosis (BV) in the region. However, little progress has been made in finding an effective cure for BV. Drawing on advances in microbiome-directed therapies for gastrointestinal disorders, similar live-biotherapeutic based approaches for BV treatment are being evaluated. Here, we summarize current knowledge regarding vaginal microbiota in BV, explore geographical differences in vaginal microbiota, and argue that novel BV therapeutics should be tailored specifically to meet the needs of African women.Recent findingsCervicovaginal microbiota dominated by Lactobacillus crispatus are optimal, although these are uncommon in African women. Besides socio-behavioural and environmental influences on the vaginal microbiota, host and microbial genetic traits should be considered, particularly those relating to glycogen metabolism. Novel microbiome-directed approaches being developed to treat BV should employ transfers of multiple microbial strains to ensure sustained colonization and BV cure.SummaryImproving the efficacy and durability of BV treatment with microbiome-directed therapies by appropriately accounting for host and microbial genetic factors, could potentially reduce the risk of HIV infection in African women.